2021
DOI: 10.1371/journal.pone.0245318
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with difficulty of hospital acceptance of patients suspected to have cerebrovascular diseases: A nationwide population-based observational study

Abstract: Although it is essential to shorten the interval to initial treatment in the care of acute ischemic stroke, some hospitals in Japan reject requests for hospital acceptance from on-scene emergency medical service personnel because of limited resources, which can cause delays in care. We aimed to assess the risk factors for difficulty of hospital acceptance of patients suspected to have cerebrovascular diseases. We conducted a retrospective analysis of the national ambulance records of the Fire and Disaster Mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This outcome could be attributed to the financial incentives hospitals received with reimbursement for ambulance transportation acceptance, and it could be an effective solution for the difficulties associated with hospital acceptance in Japan. Previous studies reported that older patient age, night-time and weekends were associated with difficulty in hospital acceptance in Japan 6 8 10. Increasing the reimbursement for ambulance transportation acceptance might be an effective solution to these difficulties.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This outcome could be attributed to the financial incentives hospitals received with reimbursement for ambulance transportation acceptance, and it could be an effective solution for the difficulties associated with hospital acceptance in Japan. Previous studies reported that older patient age, night-time and weekends were associated with difficulty in hospital acceptance in Japan 6 8 10. Increasing the reimbursement for ambulance transportation acceptance might be an effective solution to these difficulties.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, our results showed that an increase in the reimbursement for ambulance transportation acceptance decreased the number of EMS calls for severe and moderate patients, which is more important in emergency medicine. In addition, the findings showed a trend toward effectiveness in the Kansai region, where the emergency room system is generally fragile and hospitals have more difficulty accepting patients, which indicates that providing financial support to accepting hospitals would be one of the possible solutions for addressing the difficulty in hospital acceptance, especially in areas where the medical system is already overstretched 8…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations